Innovation of Technology-Based Learning Models to Increase Student Involvement in Distance Learning in Islamic Higher Education - Latifah, Ella Dewi; Asmadi, Iwan; Yanuarsari, Revita (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2025)
Distance learning in various educational institutions poses significant challenges in creating effective interaction between lecturers and students. This study aims to analyze the implementation of technology-based learning model innovations to enhance student engagement in the Islamic Religious Education (PAI) Study Program at STAI Al-Falah Cicalengka, Bandung. A mixed-method descriptive approach was employed, combining quantitative and qualitative data obtained through interviews, observations, documentation, and questionnaires.  Statistical analysis showed a correlation coefficient of 0.85, indicating a strong positive relationship between student engagement and the use of technology in learning. These results suggest that technology-based learning model innovations can optimize the learning experience and improve the quality of education in Islamic higher education.